Women as Food Producers: A Comparison with Male Counterpart - Eyemoon, Eashrat Jahan (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2017)
The aim of the study is to explore the role of women and their male counterparts in food production in rural area in developing countries which was examined by selecting 120 samples (60 men and 60 women) purposively from a village of Bangladesh named Hasangonj for sample survey. The main objectives of the study is to know the role of men and women in food production in rural Bangladesh and to outline a comparison between their roles. The finding reveals that the contribution of women in food production is very significant with the men farmer. In some cases, men are less engaged with the production of some significant sector like poultry raising, livestock raising, homestead crops etc. Men are more important in producing field crops as women are generally confined at home culturally. The involvement of men is more significant in case of monetized related activities while women continuously provide their labor to produce food for households ultimately for nations. In the sector of homestead farming, field cultivation, livestock rearing, poultry raising, fisheries the role of women is very significant when the role of men are mostly noticed in field cultivation